The Influence of The Regional Revenue and Expenditure Budget (APBD) on Poverty in Simalungun District - Pinondang Nainggolan; Anggiat Sinurat (Institute of Computer Science (IOCS), 2021)
The influence of regional APBD revenue and expenditure budgets on poverty in Simalungun Regency. This research was conducted in Simalungun Regency with the aim of analyzing the influence of the APBD on the poor population of Simalungun Regency. The results of this study are : 1).The APBD of Simalungun Regency has a positive and significant effect on the growth of PDRB in Simalungun Regency. The APBD regression coefficient value for GRDP growth is 0.0008 which means that every 1 billion rupiah increase in the APBD of Simalungun Regency will have an effect on the increase in the GRDP growth of Simalungun Regency by 0.0008 billion rupiah or every increase in the Regional Budget of Simalugn Regency of 1 billion rupiah will have an impact on an increase in the APBD growth of Simalungun Regency by 0.8%. This means that the greater the growth of the Simalungun Regency APBD, the greater the growth rate of Simalungun Regency. 2) The Regional Budget of Simalungun Regency does not have a positive effect on the growth of the poor in Simalungun Regency. The APBD regression coefficient value for the poor is -7.405, which means that every 1 billion increase in the APBD of Simalungun Regency will reduce the number of poor people in Simalungun Regency by 7,405 people. This means that the greater the amount of APBD expenditure in Simalungun Regency, the less the number of poor people will be.